2001
DOI: 10.1111/j.8755-8920.2001.450507.x
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Trichomoniasis as a Model for Development of Vaccines against Sexually‐transmitted Disease

Abstract: Systemic immunization or systemic priming with local boosting protects against bovine trichomoniasis via IgG or IgA antibodies (respectively) to a major surface antigen of trichomonads. Immunization of the genital mucosa results in formation of inductive sites for a local IgA response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 17 publications
2
46
1
Order By: Relevance
“…Luna's stain. Bar ϭ 100 m. thelial inflammatory infiltrates in uterine trichomoniasis, 10 the association with uterine IgE responses has not been reported in trichomoniasis, to our knowledge. Similarly, mast cell and IgE antibodies specific for T. foetus or TF 1.17 antigen have not been reported before.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Luna's stain. Bar ϭ 100 m. thelial inflammatory infiltrates in uterine trichomoniasis, 10 the association with uterine IgE responses has not been reported in trichomoniasis, to our knowledge. Similarly, mast cell and IgE antibodies specific for T. foetus or TF 1.17 antigen have not been reported before.…”
Section: Discussionmentioning
confidence: 71%
“…In our studies of virgin noninfected heifers, lymphoid follicles were not seen in the uterine mucosa but, in infected heifers, accumulations of immunocytes, lymphoid nodules, and follicles (some with germinal centers) were detected under the epithelium and adjacent to infected glands. 2,9,10 We concluded that uterine inductive sites develop after antigenic stimulation. Several questions arise.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Namely, sialomucins and sulfomucins represent the main glycoproteins in the mucus (18), whose pH simulates the pH in the vaginal tract of post-menopausal women (pH is 6-7.5 in cow and as high as 7 in post-menopausal women; 2,19). The important role of bovine mucosa and mucus as in vitro models have been illustrated in several studies addressing topical and systemic drug delivery, adhesion of Lactobacillus to the epithelium, sperm transport through the mucus, and immunization by vaginal route (19)(20)(21)(22)(23)(24)(25)(26). More frequent use of bovine tissue is not just the consequence of the above stated similarities, but also results from the ease of obtaining multiple and large samples on regular basis at relatively low cost.…”
Section: Introductionmentioning
confidence: 99%